Sasak Women in Contemporary Da'wah: A Case Study of Sitti Raihanun Zainuddin Abdul Madjid's Role at Syaikh Zainuddin NW Anjani Islamic Boarding School - Suhardi; Fahrurrozi; Abdul Malik (LPPM Stikosa - AWS, 2024)
This study highlights the urgent role of Sasak women in contemporary da'wah, focusing on the contributions of Sitti Raihanun Zainuddin Abdul Madjid at Syaikh Zainuddin NW Anjani Islamic Boarding School. The aim of this research is to explore Sitti Raihanun's contributions in developing education-based da'wah, particularly in empowering women through religious education. This research employs a qualitative approach with a case study design. Data collection techniques include in-depth interviews, observations, and documentation, while data analysis is conducted using thematic analysis. The findings reveal that Sitti Raihanun plays a central role in aligning traditional Sasak values with contemporary da'wah, enabling the advancement of religious education for women. Despite facing challenges such as gender stereotypes and socio-cultural barriers, she effectively utilizes support from religious institutions and communities to expand her da'wah influence. This study concludes that the role of Sasak women in contemporary da'wah is crucial in strengthening religious education and empowering women in Lombok. The implications of this study highlight the importance of empowering women in da'wah as a strategy to create more inclusive and sustainable social change in society